A Comparative microleakage analysis of two bioactive root perforation sealing materials - Indriani, Herliena Dyah; Rinastiti, Margareta; Untara, Raphael Tri Endra (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Complications during root canal therapy, such as perforation, might lead to failure of root canal therapy. A root perforation allows the root canal system and periradicular tissue to communicate, which may affect the treatment outcome. The ability of perforated sealing materials to stop microleakage is also crucial to the success of the treatment. The latest bioactive materials, such as bioactive calcium silicate cement (BCSC) and enhanced resin-modified glass ionomer (ERMGIC), are used. This study compares the microleakage of BCSC and ERMGIC as a material for sealing root perforations at different observation times. Thirty post-extraction premolars, no caries, and single roots were used in this study. Samples were divided into two different groups. The perforation simulation was created using cylindrical fissure round-end burs at a distance of 2 mm from the cervical line. Following the use of BCSC and ERMGIC to seal the perforation, the samples were separated into three subgroups and immersed in a simulated body fluid for different durations in an incubator set at 37°C. As soon as the samples reached the immersion period, all samples were immersed in 1% methylene blue for 24 hours. It was then divided into two parts and examined under a microscope at 50x magnification. The two-way ANOVA test demonstrated no significant variation in the microleakage of the root perforation seal, depending on the material type and the observation time. This study found that microleakage, a material used to seal root perforations, was unaffected by the types of materials used or the length of the observation period.